2020
DOI: 10.3390/genes11040381
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Sequencing of a Forensic STR Multiplex Reveals Loci Suitable for Single-Contributor STR Profiling

Abstract: Nanopore sequencing for forensic short tandem repeats (STR) genotyping comes with the advantages associated with massively parallel sequencing (MPS) without the need for a high up-front device cost, but genotyping is inaccurate, partially due to the occurrence of homopolymers in STR loci. The goal of this study was to apply the latest progress in nanopore sequencing by Oxford Nanopore Technologies in the field of STR genotyping. The experiments were performed using the state of the art R9.4 flow cell and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 19 publications
3
44
0
Order By: Relevance
“…A summary of the NGS and traditional method-based genotyping results for all samples is shown in Supplementary Tables S6–S9 . These results confirmed the accuracy of both the NGS and CE methods [ 27 ].…”
Section: Resultssupporting
confidence: 79%
“…A summary of the NGS and traditional method-based genotyping results for all samples is shown in Supplementary Tables S6–S9 . These results confirmed the accuracy of both the NGS and CE methods [ 27 ].…”
Section: Resultssupporting
confidence: 79%
“…Improvements in base-calling accuracy are constantly contributing to reduce this type of errors, with Bonito now representing a very promising base-caller [45,46]. Moreover, the R10.3 chemistry recently released by ONT is expected to improve the accuracy of indel calling because it uses pores with a longer barrel and a dual reader head, which achieves better raw read accuracy even in homopolymer regions [44,47]. Although indel calling from R9.4 data is not yet accurate, we showed that ONT reads can be used to accurately phase both SNVs and indels when these have already been identified using a more accurate sequencing approach (such as Illumina or Sanger).…”
Section: Discussionmentioning
confidence: 99%
“…A drawback of current forensic DNA technology is the need for cumbersome equipment, making it difficult to operate outside the laboratory environment. Transitioning forensic DNA analysis from the laboratory to the scene of an incident should deliver wide-ranging benefits in terms of the speed of result delivery, reduced contamination risk, and more efficient staff training [ 4 , 5 ]. Oxford Nanopore Technologies (ONT) developed the MinION, a long-read sequencer powered by USB.…”
mentioning
confidence: 99%
“…Oxford Nanopore Technologies (ONT) developed the MinION, a long-read sequencer powered by USB. Its small size and portability make it ideal for remote analysis [ 4 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation